Development of Module for Strengthening Pancasila Student Profiles Project on the Theme of Sustainable Lifestyle Through Solid Soap Production from Used Cooking Oil - Rini Nurmiyati; Hairida; Masriani; Fitria Arifiyanti (Universitas Syiah Kuala, 2026)
Repeated use of cooking oil can degrade food quality and potentially lead to adverse health effects and environmental impacts. Therefore, early education on the management of used cooking oil is necessary through the pancasila student profile strengthening project (P5). This study aims to develop a P5 project module that focuses on producing soap from used cooking oil, suitable for use in the learning process. The research employed a research and development (R&D) approach utilizing the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. However, this study was limited to the development stage. The developed module was validated by two content experts, two media experts, and two language experts. In addition, response questionnaires were distributed to three teachers and 33 students. The validation results showed a score of 100% from both content and media experts, while the language experts’ validation reached 90.6%. The teachers’ responses to the developed module achieved a score of 100%, whereas students’ responses reached 86.5%. Based on these results, it can be concluded that the P5 module is “highly feasible” for use in the learning process and received very positive responses from both teachers and students